Structural Performance of Fiber-Reinforced Cementitious Composite Members Reinforced with Fiber-Reinforced Polymer Bars: A Systematic Review - Helen Negash Shiferaw; Toshiyuki Kanakubo (Applied Sciences, 2025)
The integration of fiber-reinforced cementitious composites (FRCCs) with fiber-reinforced polymer (FRP) bars represents a significant advancement in concrete technology, aimed at enhancing the structural performance of reinforced concrete elements. The incorporation of fibers into cementitious composites markedly improves their mechanical properties, including tensile strength, ductility, compressive strength, and flexural strength, by effectively bridging cracks and optimizing load distribution. Furthermore, FRP bars extend these properties with their high tensile strength, lightweight characteristics, and exceptional corrosion resistance, rendering them ideal for applications in aggressive environments. In recent years, there has been a notable increase in interest from the engineering research community regarding this topic, primarily to solve the issues of aging and deteriorating infrastructure. Researchers have conducted extensive investigations into the structural performance of FRCC and FRP composite systems. This paper presents a systematic literature review that surveys experimental and analytical studies, findings, and emerging trends in this field. A comprehensive search on the Web of Science identified 40 relevant research articles through a rigorous selection process. Key factors of structural performance, such as bond behavior, flexural behavior, ductility performance assessments, shear and torsional performance, and durability evaluations, have been documented. This review aims to provide an in-depth understanding of the structural performance of these innovative composite materials, paving the way for future research and development in construction materials technology.